Physico-Chemical Characterization of Composite Flour from Sweet Potato Flour, Corn Starch, and Soybean Flour - Iman Ginting; Elisa Julianti; Rona J Nainggolan (Jurnal Rekayasa Pangan dan Pertanian, 2015)
This research aims at evaluating the physicochemical properties of composite flour produced from sweet potato flour, corn starch, soybean flour, and xanthan gum. . The research had been performed using factorial completely randomized design, with one factor i.e  ratio of sweet potato flour : corn starch : soybean flour : xanthan gum : 60%:20%:19,5%:0,5%, 50%:30%:19,5%:0,5%, 40%:40%:19,5%:0,5%, 50%:20%:29,5%:0,5%,  40%:30%:29,5%:0,5%, 30%:40%:29,5%:0,5% and 100% wheat flour as control.  The composite flour produces were subjected to chemical analysis (proximate and crude fiber).  The results showed  that ratio of sweet potato flour, corn starch, soybean flour, and xanthan gum gave the high significant differences (P<0,01) on all of parameter observed.  Based on protein content,  the composite flour with the proportion of sweet potato 30%, corn starch 40%, soybean flour 29,5% and xanthan gum 0,5%  can be considered similar to wheat flour for making wheatless products. Keyword : Composite flour,  sweet potato, corn starch,  soybean flour, xanthan gum